Landscape evolution in China’s key ecological function zones during 1990–2015 - Liu, Jiafeng; Zhong, Jing (Scientific reports, 2024)
Landscape evolution has profound effects on ecosystems. Recently, some studies suggest that China has implemented plans leading in the greening of the world by mainly describing the changes based on satellite data. However, few studies have analyzed the policy effect on ecosystem improvement from the perspective of landscape pattern evolution. Among the numerous ecological policy plans, China’s key ecological function zones plan is an important one. In this study, we focus on depicting the long-term and large-scale landscape evolution in China’s key ecological function zones, which are accounting for 40.2% of China’s land area, and include four-type ecoregions where ecosystems are fragile or important, to comprehensively explore the environmental influences of policy planning. For this purpose, we first described the landscape composition changes and conversion mechanisms in China’s key ecological function zones from 1990 to 2015. Then we captured the detailed pattern evolution characteristics by landscape indices. The results show that these ecoregions were mostly evolving in an unfavorable direction in these 25 years, i.e. destruction of habitats and increment of fragmentation. Although greening areas increased based on other recent researches, the landscape pattern became worse, indicating it is necessary for the detailed analysis of landscape ecology and more accurate ecological planning. We also found the deterioration of the ecological environment had been uncharacteristically stopped or even improved in wind prevention and sand fixation ecoregions and biodiversity maintenance ecoregions after the implementation of this plan. Furthermore, we assumed that the policy is more prominent in these prohibiting sabotages and protecting areas with fragile ecological bases, which may be caused by the differentiated transfer payments in different ecoregions. Finally, some planning suggestions, such as stricter land use control, the regional balance of ecological transfer payments and deepening of ecological migration policies, etc., were proposed for promoting better future environmental changes.